Cost and accuracy analysis of group and individual testing strategies: Implications for COVID 19 - Islam, Ismat (My University, 2021)
We compared several group and individual testing strategies in terms of cost and accuracy and then showed which one is more accurate while costing as little as possible for a specified prevalence rate.
Keywords: Group testing, Individual Testing, prevalence rate; Screening, Cost, Accuracy, Error